Hubungan Partus Lama dan Berat Badan Lahir Bayi dengan Robekan Perineum Pada Ibu Bersalin di Puskesmas Wara Kota Palopo - Fitri H. Sudiamin; Fadliyah Fadliyah (Jurnal Ventilator, 2023)
A perineal tear is a tear that occurs at the time the baby is born either spontaneously or with a tool or action. The impact of perineal tears can result in continuous bleeding and infection of suture wounds in the birth canal, slow treatment can cause death in postpartum mothers to find out the relationship between the old partus and the baby's birth weight with perineal tears in pregnant women at the Wara Health Center, Palopo City in 2021. This study is a quantitative analytical research with a "cross sectional study" design. The population in this study is maternity mothers in the working area of the Wara Health Center, Palopo City. Sampling in this study uses a total sampling technique. Data collection uses questionnaires. The data that has been collected is then processed and analyzed using a laptop using Microsoft excel programs and statistical programs (SPSS). Data analysis includes univariate analysis by looking for frequency distribution and bivariate analysis with chi square test with significance level (.05). There was a relationship between the old partus and the incidence of perineal tears (p=0.020) and there was a relationship between the baby's birth weight and the incidence of perineal tears (p=0.007). There is a relationship between the old partus and the baby's birth weight with perineal tears in pregnant women at the Wara Health Center, Palopo City in 2021. for midwives in observing childbirth using a partograph is expected to be carried out well and be able to identify quickly and accurately to further increase vigilance in carrying out childbirth help so that perineal tears do not occur.